Law, society, and history : themes in the legal sociology and legal history of Lawrence M. Friedman / edited by Robert W. Gordon, Morton J. Horwitz. - Gordon, Robert W. (Robert Watson), 1941-; Horwitz, Morton J., 1938- (Cambridge studies in law and society., 2011)
This book assembles essays on legal sociology and legal history by an international group of distinguished scholars. All of them have been influenced by the eminent and prolific legal historian, legal sociologist and scholar of comparative law, Lawrence M. Friedman. Not just a Festschrift of essays by colleagues and disciples, this volume presents a sustained examination and application of Friedman's ideas and methods. Together, the essays in this volume show the powerful ripple effects of Friedman's work on American and comparative legal sociology, American and comparative legal history and the general sociology of law and legal change.